Between endowment and entitlement on the access to healthcare: acts of citizenship of undocumented migrant women in the Sicilian healthcare system - Pascoal, Rafaela (Frontiers in Human Dynamics, 2025)
Migrant women’s wellbeing and access to health are particularly impacted by gender inequality and discrimination, traditional female roles, gendered labour market, gender-based violence and feminization of poverty. From an intersectional lens, undocumented migrant women are at the lowest tier in the hierarchy of healthcare access. This research explores the nexus of irregular migration and health spheres in a gender perspective, focusing in particular on the undocumented migrant women’s acts of citizenship. Based on the theoretical framework of fundamental causes, this research analyses the perception of street level bureaucrats, through the conduction of fifteen semi-structured interviews, in 2024–2025, on the endowment to health assets of undocumented migrant women in Sicily, by answering the following research questions: (1) how the undocumented status of migrant women affects their endowment in accessing healthcare?; (2) in what way does the socioeconomic status influence the access of undocumented migrant women to health? and (3) how can undocumented migrant women’s social capital enhance their endowment to health? The research confirms the existence of fundamental causes hindering undocumented migrant women’s access to healthcare, especially regarding the low socioeconomic status and cultural capital of the receiving country. The cause, as low economic status, influences multiple disease outcomes and enhances differential vulnerabilities of undocumented migrant women. In particular, practitioners reported the incidence of precarious housing and working conditions in women’s health.